2015
DOI: 10.1371/journal.pone.0132633
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Hydroxyapatite Nanocrystals with Lactoferrin as a Promising Strategy to Fine Regulate Bone Homeostasis

Abstract: Lactoferrin (LF) is an interesting glycoprotein in the field of bone biology for its regulatory effect on cells involved in bone remodeling, that results compromised in several pathological conditions, as osteoporosis. In a previous study we observed that the coupling of LF and biomimetic hydroxyapatite nanocrystals (HA), a material well-known for its bioactivity and osteoconductive properties, leads to a combined effect in the induction of osteogenic differentiation of mesenchymal stem cells. On the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…The in vitro study confirmed also that the Sr 2+ released from Sr-BCs exerts its inhibitory effect on the expression of the principal genes involved in OCLs activity (Oscar and CtsK) [ 51 53 ]. Although Itgβ3 mRNA level seems to follow the same trend of decreasing over the time of culture, no statistically difference was observed, probably due to the proved role of integrin β3 in the interaction with apatitic structure [ 54 ]. In fact, Itgβ3 is considered the principal receptor in osteoclasts mechanisms involved in adhesion to the extracellular matrix, motility and activity.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro study confirmed also that the Sr 2+ released from Sr-BCs exerts its inhibitory effect on the expression of the principal genes involved in OCLs activity (Oscar and CtsK) [ 51 53 ]. Although Itgβ3 mRNA level seems to follow the same trend of decreasing over the time of culture, no statistically difference was observed, probably due to the proved role of integrin β3 in the interaction with apatitic structure [ 54 ]. In fact, Itgβ3 is considered the principal receptor in osteoclasts mechanisms involved in adhesion to the extracellular matrix, motility and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin is a glycoprotein that has an anabolic effect on bone by promoting osteoblast proliferation and differentiation as well as decreasing osteoclast formation (Lorget et al, 2002 ; Zhang et al, 2014 ). By coupling it to hydroxyapatite nanocrystals, Montesi et al showed that these two compounds can synergistically act as a bone anabolic by increasing OSX and IBSP mRNA expression in osteoblasts, reducing osteoclast formation, and downregulating OSCAR and CTSK mRNA expression in co-cultures of MC3T3-E1 and RAW264.7 (Montesi et al, 2015 ).…”
Section: Modulators Of Remodellingmentioning
confidence: 99%
“…Moreover, HA in combination with other growth factors, proteins or polymers has been used for studying the influence on both inflammatory and osteogenic responses. Thus, different studies have been performed with Lf-HA functionalized nanocrystals [50,51] revealing this combination as a promising system with anti-inflammatory properties and increased osteogenic capacity. It has been proved that biomimetic HA nanocrystals surface-functionalized with Lf have antibacterial activity effective against Gram-positive and Gram-negative bacteria [52][53][54].…”
Section: Of 19mentioning
confidence: 99%